Farmer perceptions, knowledge, and management of fall armyworm in maize production in Uganda - Odong, Thomas Lapaka; Obongo, Isaac; Ariong, Richard; Adur, Stella E.; Adumo, Stella A.; Onen, Denish Oyaro; Rwotonen, Bob I.; Otim, Michael H. (Frontiers in Insect Science, 2024)
Spodoptera frugiperda (J.E. Smith), fall armyworm (FAW), a polyphagous Noctuid pest, was first reported in Uganda in 2016. Farmers were trained to identify and manage the pest, but there was a lack of information on farmer knowledge, perceptions and practices deployed to control it. Therefore, we conducted a survey to assess maize farmers' knowledge, perceptions and management of the pest during the invasion. One thousand two hundred eighty-nine maize farmers from 10 maize-growing agro-ecological zones (AEZ) of Uganda were interviewed using well-structured questionnaires. The data were analyzed using R version 4.2.3. The respondents faced many constraints, including pests, drought, poor soils and labour constraints. Among the pests, FAW was ranked by most (85%) of the respondents as the number one pest problem in maize, and some farmers reported having noticed it way back in 2014. By 2018, more than 90% of the farmers had seen or heard about FAW, and about 80% saw FAW in their fields. The most common FAW symptoms reported by maize farmers were windowing, near tunnel damage, and holes on the cobs. The developmental stages of FAW identified by farmers included eggs (10%), young larvae (78.7%), mature larvae (73.5%) and adult moths (6.7%). Insecticides were the major control tactic, although some farmers used plant extracts, hand-picking, sand, and ash. Farmers sourced information on FAW from various sources, including fellow farmers, radio/TV, extension agents, input dealers, print media, research and NGO extension. There is a need to package clear and uniform information for the farmers and to develop and promote a sustainable solution for FAW management, including harnessing biological control and cultural practices.